(untitled) (Medical Forum Monthly, 2024)
Background: Child-Pugh classification currently remains the most important parameter to determine liver function in patients of chronic liver disease (CLD). This study was carried out to find a relationship between abnormal Liver Function Tests (LFTs) and extent of liver damage in patients of CLD grouped as Child class A and B. Aims and objectives: To find a relationship between LFTs and severity of liver disease assessed by Child-Pugh scoring. Study Design: Retrospective study. Place and Duration of Study: This study was conducted at the Medical Words of Services Hospital, Lahore from February 2009 to June 2009. Materials and Methods: It was a retrospective analysis of 40 patients aged 17-74 with CLD. Patients were selected from medical wards of Services Hospital Lahore. Patients were classified as Child class A and B on the basis of severity of liver function. Liver function tests including prothrombin time(PT), serum bilirubin, enzymes like Alkaline Phosphatase (ALP), Aspartate Transaminase (AST), Alanine Transaminase (ALT), serum Proteins and Albumin concentrations were performed by standard laboratory methods. Results: It was observed that serum level of ALP, ALT, AST and the AST/ ALT ratio as well as prothrombin time were significantly increased in patients as compared to their controls. On the other hand level of total proteins and albumin were significantly decreased in patients as compared to their controls whereas the level of bilirubin remains insignificant. In Child class B patients the levels of serum bilirubin, ALP, ALT, AST and ratio AST/ALT were increased as compared to these parameters in Child class A patients. It was observed that level of serum ALP and ALT were non significantly and level of serum bilirubin, AST and AST/ALT ratio were significantly increased in Child class B patients as compared to the patients of Child class A. On the other hand level of serum total proteins and albumin were significantly decreased in Child class B patients as compared to patients of Child class A. Prothromin time is significantly increased in Child class B patients as compared to the patients of Child class A. Conclusion: Further deterioration in LFTs may warn a clinician about progress of disease in a patient of CLD and to further investigate about the liver function at that stage.